(untitled) (The Agriculturists, 2019)
Waterlogging is one the major abiotic stresses that affects growth and yield of blackgram. A field experiment was carried out at the experimental field of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, 1706 during kharif II season to evaluate 26 blackgram genotypes for understanding the flood tolerance in respect of yield and yield contributing characters. The experiment was laid out with a randomized complete block design with three replications. Water logging depth was 3-5 cm, created by irrigation from tap water and imposed at 29 days after emergence of seedlings which was maintained for 8 days. Multivariate analysis was performed involving eight qualitative plant characters. A wide range of variation was found for all the qualitative plant characters like plant height, plant dry weight, branches per plant, pods per plant, pod length, seeds per pod, 1000-seed weight and yield per plant. Flooding reduced all the growth parameters of blackgram but degree of reduction varied greatly over the blackgram genotypes. Considering yield performance, the genotypes BU Acc 25 showed the highest yield per plant (9.03 g) followed by the BU Acc 17 (6.47 g) and BU Acc 24 (6.17) under flooding . The yield reduction percent of the same genotypes were minimum (43.86, 60.82 and 65.96, respectively) compared to control which is very important for selection of those genotypes as a flooding tolerant. The Agriculturists 2019; 17(1-2) 89-101